Evaluation of Adsorption Efficiency of Ferronia elefuntum Fruit Shell for Methylene Blue from Aqueous Solution - Chaudhari, U.E. (Asian Journal of Chemistry, 2010)
Methylene blue adsorption from an aqueous solution on to Ferronia elefuntum fruit shell (FEFS) has been studied experimentally using the batch adsorption method. The operating variables studied are pH, initial dye concentration contact time. Adsorption isotherm (Langmuir and Freundlich) and kinetics model were studied. The adsorption capacity of FEFS was found to increasing with increase in temperature, thermody-namics parameters such as DG, DH and DS for adsorption were evaluated. Adsorption of methylene blue on FEFS found to be endothermic process. The aim of present work is to study the effectiveness of the adsorbent to remove dyes from their aqueous solution and the removal of colour from textile and various industrial wastewater.